2021
DOI: 10.30598/tsiam.2021.1.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bird species in Wetlands around Siran Lake, Muara Kaman, Central Mahakam, East Kalimantan

Abstract: The avifauna of tropical peat swamp forests in East Kalimantan has not been well documented because of the smallest peat area compared to central Kalimantan. The surveys were conducted using various methods in the Muara Siran peat swamp forests and surrounding areas of Lake Siran (heath forest and riparian) in East Kalimantan, Indonesia. These findings were recorded on a list of 80 bird species as well as in numerous noteworthy records.  Wetlands are an essential habitat for many threatened and near-threatened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Observations showed that many bird species, including the Oriental Darter, use the remaining mangrove trees without leaves for perching and sunbathing. The Grey-Headed Fish Eagle (Ichthyophaga ichtyacheus) was commonly found in peat and lake areas [7]. It had also been found in mangrove areas in the Mahakam Delta.…”
Section: Waterbird Diversitymentioning
confidence: 99%
“…Observations showed that many bird species, including the Oriental Darter, use the remaining mangrove trees without leaves for perching and sunbathing. The Grey-Headed Fish Eagle (Ichthyophaga ichtyacheus) was commonly found in peat and lake areas [7]. It had also been found in mangrove areas in the Mahakam Delta.…”
Section: Waterbird Diversitymentioning
confidence: 99%